Grain Discolouration Disease Complex of Rice: Assessment and Management of Infested Grains Using Fungicides - Maji, E.A; Imolehin, E. D (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
Rice grain discoloration complex disease is threatening the crop all over the world and its of great importance because it leads to quality loss at harvest. So the present study was carried out to identify different fungi associated with this complex disease and management of infested rice seeds though fungicides. For this purpose, discolored grain samples were collected and different fungi were isolated. Identification of isolated fungi was done on the basis of their morphological characters and purified culture of each fungus was prepared. Pathogenecity test was carried out in-vitro and in-vivo using the percentage incidence calculation to confirm the involvement of fungi. Statistical results illustrated that the homogenous mixture of spore suspension contains fungal spores of Fusarium spp, Tricoderma, Aspergillus flavus, Aspergilus niger, Helmithosporium, Cercospora, Alternaria, Bipolaris and Curvularia of rice proven most lethal in showing the maximum symptoms in-vitro and in-vivo. Statistical data for seed germination exhibited that Carbendazim and Diathene-M45 were comparatively better and improved percentage seed germination up to considerable levels followed by Redomil, Topsin-M and Cordate respectively.